New study on the 1941 Gloria Fault earthquake and tsunami - Baptista, Maria Ana Carvalho Viana (2017)
The M ∼ 8.3–8.4 25 November 1941 was one of the largest submarine strike-slip earthquakes ever recorded in the Northeast (NE) Atlantic basin. This event occurred along the Eurasia–Nubia plate boundary between the Azores and the Strait of Gibraltar. After the earthquake, the tide stations in the NE Atlantic recorded a small tsunami with maximum amplitudes of 40 cm peak to through in the Azores and Madeira islands. In this study, we present a re-evaluation of the earthquake epicentre location using seismological data not included in previous studies. We invert the tsunami travel times to obtain a preliminary tsunami source location using the backward ray tracing (BRT) technique. We invert the tsunami waveforms to infer the initial sea surface displacement using empirical Green’s functions, without prior assumptions about the geometry of the source. The results of the BRT simulation locate the tsunami source quite close to the new epicentre. This fact suggests that the co-seismic deformation of the earthquake induced the tsunami. The waveform inversion of tsunami data favours the conclusion that the earthquake ruptured an approximately 160 km segment of the plate boundary, in the eastern section of the Gloria Fault between −20.249 and −18.630◦ E. The results presented here contribute to the evaluation of tsunami hazard in the Northeast Atlantic basin.